Integrasi Nilai-Nilai Pancasila Berbasis Kearifan Lokal Masyarakat Lamaholot Dalam Pembentukan Karakter Peserta Didik - Yulius Rustan Effendi; Engelbertus Kukuh Widijatmoko; Emanuel Asdiakon Baowolo (Universitas Muhammadiyah Ponorogo, 2026)
This study stems from an effort to understand how the local wisdom of the Lamaholot community is utilized as a medium for instilling Pancasila values within the school environment of SMAK Lamaholot Witihama. The research focuses on the process of students’ character formation, which takes place through the interaction of local culture, the school environment, and learning activities. To gain a comprehensive understanding of this process, the study employed a qualitative approach with an ethnographic design. Research data were collected through direct observation of school activities, in-depth interviews with various stakeholders, and the examination of documents related to the implementation of character education. The findings reveal that several cultural values embedded within the Lamaholot community, including Nobo Lema, gemohing, soka lewo, and Roba Witi, share substantial similarities with the principles embodied in Pancasila. These values are not only introduced through formal classroom instruction but are also reflected in school routines, cultural traditions, and the implementation of the Pancasila Student Profile Strengthening Project (P5). The presence of these cultural values in various school activities provides students with opportunities to practice religious attitudes, social awareness, responsibility, cooperation, and democratic behavior in their daily lives. The study further indicates that the sustainability of value internalization is strongly influenced by the involvement of indigenous communities, the support of school members, and the consistent implementation of school cultural practices.